2019
DOI: 10.1016/j.jalz.2019.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Clinical relevance of the dichotomous classification of Alzheimer's disease biomarkers: Should there be a “gray zone”?

Abstract: The 2018 National Institute on Aging and the Alzheimer's Association (NIA-AA) research framework recently redefined Alzheimer's disease (AD) as a biological construct, based on in vivo biomarkers reflecting key neuropathologic features. Combinations of normal/abnormal levels of three biomarker categories, based on single thresholds, form the AD signature profile that defines the biological disease state as a continuum, independent of clinical symptomatology. While single thresholds may be useful in defining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Our demonstration of the potential significance of grey zone amyloid burden may have several clinical consequences. Especially for individuals with amyloid burden within the grey zone, a single threshold might not be very good at distinguishing individuals with a high and a low risk of cognitive decline [4,40]. When a binary division is warranted, our results imply that only lower thresholds that include the grey zone capture all individuals at risk of memory decline, which corresponds to a previous study that showed existing thresholds for Pittsburgh compound B (PIB) seem too high [24].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our demonstration of the potential significance of grey zone amyloid burden may have several clinical consequences. Especially for individuals with amyloid burden within the grey zone, a single threshold might not be very good at distinguishing individuals with a high and a low risk of cognitive decline [4,40]. When a binary division is warranted, our results imply that only lower thresholds that include the grey zone capture all individuals at risk of memory decline, which corresponds to a previous study that showed existing thresholds for Pittsburgh compound B (PIB) seem too high [24].…”
Section: Discussionsupporting
confidence: 63%
“…Studies that focused on peri-or subthreshold amyloid levels have had different approaches, for example studying amyloid negative subthreshold individuals [25,26,38], or CSF/PET discordant cases [39]. In a recent article, the grey zone is proposed as a region of uncertainty around the threshold for which more data is needed to actually estimate the risk of cognitive decline or clinical progression [40]. These Cohen's kappa was used to determine the degree of concordance between visual assessment and the six different thresholds BP ND binding potential, GMM Gaussian mixture modelling, SUVr standardized uptake value ratio previous studies found that individuals in the subthreshold range can be on the path to further neurodegeneration (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We note that three MCI and one AD participant did not meet criteria for amyloid-positivity. However, dichotomized AD risk has recently been questioned [46], as biomarker sensitivity may improve when assessed as a continuum, with even subthreshold amyloid levels predicting subsequent AD pathology [47]. Though we cannot rule out the presence of non-AD etiology, or subthreshold AD pathology, in our amyloidnegative group, this would not preclude our finding that microstructure predicts cognitive impairment regardless of amyloid.…”
Section: Discussionmentioning
confidence: 85%
“…We have analysed a subset of the ADNI population which is at a higher risk of developing AD in the future, on the basis of the amyloid levels at baseline. For this we have used strict dichotomous cut-offs and acknowledge that this itself comes with limitations of not being able to clearly distinguish between individuals near the cut-off level set in the analyses 29 . This assumption simpli es the complex realities of the dynamical behaviour of the biomarkers.…”
Section: Discussionmentioning
confidence: 99%